1994
DOI: 10.1002/gps.930090406
|View full text |Cite
|
Sign up to set email alerts
|

Residential care as an alternative to long‐stay hospital: A cost‐effectiveness evaluation of two pilot projects

Abstract: SUMMARYTwo projects were established to help elderly people with mental health problems move from continuing care hospital wards to local authority residential care homes. The projects were part of a larger programme established in the 1980s to test new policy and practice options. Each hospital resident was interviewed and assessed prior to commencing any programme of activities designed to prepare them for resettlement in the community. Data came from hospital patients themselves, from staff and from intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…The least support need was for Community Presence, the mean rating being "a bit of help". This is congruent with hospital closure studies that found physical integration was more successful than social integration (Knapp et al, 1992;Leff, 1995). It was likely that this population was deeply excluded.…”
Section: Which Needs Required What Levels Of Support?supporting
confidence: 81%
See 1 more Smart Citation
“…The least support need was for Community Presence, the mean rating being "a bit of help". This is congruent with hospital closure studies that found physical integration was more successful than social integration (Knapp et al, 1992;Leff, 1995). It was likely that this population was deeply excluded.…”
Section: Which Needs Required What Levels Of Support?supporting
confidence: 81%
“…Within the context of necessary methodological limitations this study has demonstrated that the SNQ can differentiate between service users' relatively low support needs to achieve community presence and high levels for community participation (Knapp et al, 1992;Leff, 1995). The SNQ has good reliability and validity in most domains, especially those derived from SRV.…”
Section: Discussionmentioning
confidence: 98%
“…There should be longer stay places for those with the most needs with regular re-assessment to see whether the resident may be able to move. This movement from long-stay placement in hospital has been associated with improved residents' quality of life (Knapp et al 1994). Thirdly, and linked to this, we would recommend that homes should cater for those with different levels of need, and be staffed appropriately, so that increasing needs does not necessarily mean residents moving.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Research into these projects (Renshaw et al, 1988;Knapp, 1992) sought to identify methods of social support for service users. Projects took different approaches, but initial support included provision for multidisciplinary individualised care planning and subsequently for services to be channelled to individual service users through a key care worker (Renshaw et al, 1988: 67-8).…”
Section: Professional and Service Developmentmentioning
confidence: 99%